2022
DOI: 10.3389/fimmu.2022.1024559
|View full text |Cite
|
Sign up to set email alerts
|

Update on mosquito bite reaction: Itch and hypersensitivity, pathophysiology, prevention, and treatment

Abstract: Mosquito bites are endured by most populations worldwide. Reactions to mosquito bites range from localized wheals and papules with associated pruritus to rare systemic reactions and anaphylaxis in certain populations. The mechanism of itch is due to introduction of mosquito saliva components into the cutaneous tissue, although the exact pathophysiology is unclear. Histamine is thought to be a key player through mosquito saliva itself or through activation of mast cells by IgE or through an IgE-independent path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…It was shared frequently that young children suffer bouts of malaria more often (have obvious and sometimes severe symptoms) than adults. Similarly, this study and others found parents and caregivers were more cautious about babies and toddlers being bitten by mosquitoes because they have a stronger reaction to bites and the potential allergy reaction from the bites [ 41 43 ]. The study revealed that bed nets are mostly used for small children because their reaction to bites is more severe than for adults.…”
Section: Discussionmentioning
confidence: 53%
“…It was shared frequently that young children suffer bouts of malaria more often (have obvious and sometimes severe symptoms) than adults. Similarly, this study and others found parents and caregivers were more cautious about babies and toddlers being bitten by mosquitoes because they have a stronger reaction to bites and the potential allergy reaction from the bites [ 41 43 ]. The study revealed that bed nets are mostly used for small children because their reaction to bites is more severe than for adults.…”
Section: Discussionmentioning
confidence: 53%
“…His research team has been focusing on neuroimmune mechanisms and clinical treatment in chronic pruritus. 32 This was followed by Sonja Staender (84 papers) and Jacek C Szepietowski (50 papers). Most of these prolific authors were from highly productive countries or institutions and showed strong collaborative relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The most published author in this field was Gil Yosipovitch from the Itch Research Center at the University of Miami, USA, with 88 publications and 3169 citations. His research team has been focusing on neuroimmune mechanisms and clinical treatment in chronic pruritus 32 . This was followed by Sonja Staender (84 papers) and Jacek C Szepietowski (50 papers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 In agreement with this, off-label use of oral sgAHs in adults and in children has been shown to decrease whealing and accompanying pruritus in placebo-controlled trials. 48 Rupatadine 10 mg is effective in reducing itching and wheals associated with mosquito bite allergy as evaluated in a double-blind, placebo-controlled study. 49 …”
Section: Reviewmentioning
confidence: 99%